Pelatihan Literasi Keuangan untuk Penguatan Serikat Pekerja: Financial Literacy Training for Strengthening Labor Unions - Daryanto Hesti Wibowo; Bambang Irawan; Fajarina Fajarina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Financial literacy among labor unions is motivated by the limited ability of union leaders to read company financial reports, resulting in a weak, reactive bargaining position in industrial relations negotiations. The outreach activity aims to strengthen unions' technical capacity by providing a basic understanding of financial reports, data-based negotiation techniques, and the use of digital technology for communication and organizational management. The program was held over one day in a blended learning format that combined concept presentations, case studies, negotiation techniques, and an introduction to financial literacy books and applications, with evaluation through pre- and post-training questionnaires and open participant feedback. The results show an increase in participants' knowledge and confidence in analyzing financial information, high appreciation for the relevance of the material and the facilitators' competence, and the emergence of concrete plans to use the training results in the union's negotiation agenda and administrative strengthening, despite obstacles such as limited access to company financial reports, management resistance to transparency, and time constraints for administrators. In conclusion, financial literacy can be an important lever for labor unions to move from a pattern of dependency to knowledge-based autonomous action. Therefore, more in-depth follow-up training, post-workshop mentoring, and the development of institutional support are needed to ensure that this capacity-building is sustainable.